Tranexamic Acid Administration During On-Pump Cardiac Surgery: A Survey of Current Practices Among Canadian Anesthetists Working in Academic Centers. (December 2017) - Spence, Jessica; Long, Steven; Tidy, Antonella; Raymer, Karen; Devereaux, P. J.; Lamy, Andre; Whitlock, Richard; Syed, Summer
Abstract : BACKGROUND: Tranexamic acid (TXA) is commonly administered during on-pump cardiac surgery to minimize bleeding. However, an optimal dosing regimen has not been described, and recent studies suggest that higher doses may be associated with seizure. Little is known about current practice among cardiac anesthetists. METHODS: We contacted all academic anesthesia departments in Canada to identify cardiac anesthetists, who represent the majority of practitioners. This group constituted our sampling frame. Information regarding participant demographics, TXA dose, and administration details were obtained by electronic survey. Responses were analyzed descriptively. To compare dose, we assumed an 80-kg patient and 3 hours of infusion time. The Kruskal-Wallis test was used to compare average dose across provinces. RESULTS: Among 341 Canadian academic cardiac anesthetists, 234 completed the survey (68.2% response rate). Among respondents, 86.3% administer TXA to all patients; 13.7% administer it to some. Most (68.4%) administer an infusion after a bolus; other modes included infusion (4.7%), single bolus (13.2%), 2 or more boluses (12.0%), or another regimen (1.7%). The mean (standard deviation) dose given was 49 mg/kg (24), with a range from 10 to 100 mg/kg. The mean dose varied across provinces from 23 to 55 mg/kg ( P = .001). CONCLUSIONS: TXA is given to nearly all patients undergoing on-pump cardiac surgery at academic hospitals in Canada. However, there is significant heterogeneity in practice between individuals and across provinces. Further research is needed to determine the TXA dose that maximizes efficacy and minimizes side effects. Abstract : Supplemental Digital Content is available in the text.Published ahead of print August 30, 2017.